Characterization of liquefied petroleum gas system : II. intermittent exhaustion operation - Zainal Zakaria, 1967-; Firas Noori Ridha; Mohd. Norani Abdul Rahman; Hanapi Mat; World Engineering Congress (2nd : 2002 : Kuching, Sarawak) (Skudai : Universiti Teknologi Malaysia, 2002)
50